MDA5 Is Critical to Host Defense during Infection with Murine Coronavirus - Zalinger, Zachary B. (J Virol, 2015)
Infection with the murine coronavirus mouse hepatitis virus (MHV) activates the pattern recognition receptors melanoma differentiation-associated gene 5 (MDA5) and Toll-like receptor 7 (TLR7) to induce transcription of type I interferon. Type I interferon is crucial for control of viral replication and spread in the natural host, but the specific contributions of MDA5 signaling to this pathway as well as to pathogenesis and subsequent immune responses are largely unknown. In this study, we use MHV infection of the liver as a model to demonstrate that MDA5 signaling is critically important for controlling MHV-induced pathology and regulation of the immune response. Mice deficient in MDA5 expression (MDA5(−/−) mice) experienced more severe disease following MHV infection, with reduced survival, increased spread of virus to additional sites of infection, and more extensive liver damage than did wild-type mice. Although type I interferon transcription decreased in MDA5(−/−) mice, the interferon-stimulated gene response remained intact. Cytokine production by innate and adaptive immune cells was largely intact in MDA5(−/−) mice, but perforin induction by natural killer cells and levels of interferon gamma, interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α) in serum were elevated. These data suggest that MDA5 signaling reduces the severity of MHV-induced disease, at least in part by reducing the intensity of the proinflammatory cytokine response. IMPORTANCE Multicellular organisms employ a wide range of sensors to detect viruses and other pathogens. One such sensor, MDA5, detects viral RNA and triggers induction of type I interferons, chemical messengers that induce inflammation and help regulate the immune responses. In this study, we sought to determine the role of MDA5 during infection with mouse hepatitis virus, a murine coronavirus used to model viral hepatitis as well as other human diseases. We found that mice lacking the MDA5 sensor were more susceptible to infection than were mice with MDA5 and experienced decreased survival. Viral replication in the liver was similar in mice with and without MDA5, but liver damage was increased in MDA5(−/−) mice, suggesting that the immune response is causing the damage. Production of several proinflammatory cytokines was elevated in MDA5(−/−) mice, suggesting that MDA5 may be responsible for keeping pathological inflammatory responses in check.